A hybrid energy storage system using compressed air and hydrogen as the energy carrier. (1st April 2020) - Bartela, Łukasz
Abstract: In this paper, an innovative concept of an energy storage system that combines the idea of energy storage, through the use of compressed air, and the idea of energy storage, through the use of hydrogen (with its further conversion to synthetic natural gas), has been proposed. The thermal integration of two sub-systems allows for efficient storage of large amounts of energy based on the use of pressure tanks with limited volumes. A thermodynamic assessment of the integrated hybrid system was carried out. For the assumed operation parameters, an energy storage efficiency value of 38.15% was obtained, which means the technology is competitive with intensively developed pure hydrogen energy storage technologies. The results obtained for the hybrid system were compared to the results obtained for three reference systems, each of which uses hydrogen generators. The first is a typical Power-to-H2 -to-Power system, which integrates hydrogen generators with a fuel cell system. The other two additionally use a compressed air energy storage installation. In the first case the compressed air energy storage system consists of a diabatic system. In the second case the compressed air energy storage system is adiabatic. The article has discussed the disadvantages and advantages of all the analyzed systems. Highlights: An energy storage concept using air and hydrogen as the energy carriers was proposed. The main thermodynamic characteristics of innovative system were determined. Advantages and disadvantages of the hybrid system were pointed out. The energy storage efficiency of the new hybrid system can reach up to 40%. Satisfactory energy capacities are obtained without large volume gas tanks.